Introduction to Philippine politics local politics, the state, nation-building, and democratization - Atienza, Maria Ela L. (Third World perspectives on politics series, 2013)
State, patronage, and local elites / Francisco A. Magno -- Beyond patron-client relations: warlordism and local politics in the Philippines / John T. Sidel -- The Robredo style: Philippine local politics in transition / Takeshi Kawanaka -- The state and industrial transformation: comparative and local insights / Temario C. Rivera -- The Philippines: the weak state and the global war on terror / Herman Joseph S. Kraft -- Muslim perspective of the Mindanao problem: contextualizing the SPCPD / Abraham P. Sakili -- Culture, social science, and the conceptualization of the Philippine nation-state / Raul Pertierra -- Redemocratization in the wake of the 1986 people power revolution: errors and dilemmas / Randolf S. David -- Toward understanding coups and civilian-military relations / Carolina G. Hernandez -- Democracy and the Philippine Left / Olle Törnquist -- A changed terrain for popular struggles / Alexander R. Magno.